Multiple Mediators of the Relations Between Caregiving Stress and Depressive Symptoms - Mausbach, Brent T (2012)
OBJECTIVE: This study tested a model for explaining how stress is associated with depressive symptoms in a sample of spouse caregivers of patients with Alzheimer’s disease. It was hypothesized that more depressive symptoms would be significantly correlated with both “primary” caregiver stressors (i.e., care recipient problem behaviors) and “secondary” stress (i.e., role overload), but that this relationship would be significantly mediated by 4 variables: a) personal mastery, b) coping self-efficacy, c) activity restriction, and d) avoidance coping. METHOD: We used an asymptotic and resampling strategy for simultaneously testing multiple mediators of the stress-to-depressive symptoms pathway. RESULTS: Greater stress was significantly related to more depressive symptoms. Increased stress was also associated with reduced personal mastery and self-efficacy, as well as increased activity restriction and avoidance coping. Finally, these four mediators accounted for a significant amount of the relationship between stress and depressive symptoms. DISCUSSION: These results suggest multiple pathways by which both primary and secondary caregiver stresses may be associated with increased depressive symptoms, and may argue for multiple treatment targets for caregiver interventions.